DDX56 inhibits PRV replication through regulation of IFN-β signaling pathway by targeting cGAS - Xie, Jingying; Li, Xiangrong; Yang, Shunyu; Yan, Zhenfang; Chen, Lei; Yang, Yanmei; Li, Dianyu; Zhang, Xiangbo; Feng, Ruofei (Frontiers in Microbiology, 2022)
Pseudorabies virus (PRV), belonging to the pathogen of Aujeszky's disease and leading great economic losses to pig industry. Re-outburst of pseudorabies implies that new control measures are urgent needed. The present study provides a candidate factor for PRV infection that DDX56 possesses the ability to inhibit PRV replication in vitro. Overexpression of DDX56 inhibited PRV genomic DNA transcription and viral titers, whereas knockdown of DDX56 promoted viral growth. Further study demonstrated DDX56 exerted its inhibitory effects on PRV proliferation through upregulating cGAS-STING induced IFN-β expression. Moreover, we found DDX56 could promote cGAS expression and there was also a direct interaction between DDX56 and cGAS. Based on this, DDX56 regulated IFN-β pathway maybe targeted at cGAS. To verify this, dowenregulated cGAS expression in DDX56 overexpression cells were performed. Resultes indicated knockdown of cGAS expression could abrogate the inhibition role of DDX56 on PRV proliferation and also weaken the effect of DDX56 on IFN-β expression. All together, our data underscore the antiviral role of DDX56 in PRV infection and these findings broaden our understandings of host factors regulating PRV proliferation.